Correlation of staging and risk factors with cardiovascular autonomic neuropathy in patients with type II diabetes mellitus - Muhanad M. Dhumad (Nature Portfolio, 2021)
Abstract The impairment of cardiovascular autonomic control among the underdiagnosed complication of diabetes mellitus (DM) with a high prevalence rate of up to 60% in type 2 DM (T2DM). Cardiac autonomic neuropathy (CAN) is an independent risk factor for cardiovascular mortality, arrhythmia, silent ischemia, any major cardiovascular event, and heart failure. We aimed to evaluate cardiovascular autonomic activity by different physiological maneuvers, study risk factors for diabetic CAN including age, gender, duration of diabetes, body mass index (BMI), and glycemic control, and correlate CAN stage with risk factors. One hundred and forty-two T2DM patients consisted of 62 males and 80 females and 100 volunteers as a control sample. Cardiac autonomic functions were assessed by Ewing's tests. Glycated hemoglobin (HbA1c), body weight, height, body mass index (BMI), and waist-hip ratio (WHR) were also measured. Cardiovascular autonomic functions and Ewing scores were significantly different in people with diabetes when compared with control healthy subjects. Ewings test values and Ewing scores were significantly different between diabetics with and without CAN and within patients with different CAN staging. People with diabetes with CAN have a significantly longer duration of disease when compared to those without CAN. A strong association has been found between CAN severity and patient age, duration of disease, HbA1c severity, and the WHR (P < 0.001) but not with BMI. The duration of disease and HbA1c level appear to be associated with the development of CAN (P = 0.001 and P = 0.008, respectively). The poorer glycemic control and the longer the duration of the disease, the higher the prevalence of CAN in T2DM. Age, duration of disease, WHR, and HbA1c are well correlated with the severity of CAN. Parasympathetic impairment is more sensitive to the detection of autonomic dysfunctions than do sympathetic impairment.